An in- vitro evaluation the effect of endodontic irrigation solutions on the microhardness of root canal dentin. (Mustansiria Dental Journal, 2018)
The aim of this study was to evaluate the effect of 5.25 sodium hypochlorite and17%EDTA on the microhardness of root canal dentin .Fifteen, maxillary incisor teeth extracted for periodontal reasons were used. Thecrowns of the teeth were removed at the CEJ. The roots were separated longitudinallyinto two segments, embedded in acrylic resin, and polished. A total of 30specimenswere divided into 3 groups of 10 teeth at random according to the irrigation solutionused: group 1: 5.25% NaOCl for 1min; group 2: 17% EDTA for 1 min; and group 3:distilled water (control). Each group was submitted to Vickers microhardnessindentation tests. The data were recorded as Vickers numbers and the results wereanalyzed statistically by using one-way ANOVA.The results showed that, irrigation with either sodium hypochlorite or EDTAdecreased the microhardness value of root dentin. Irrigation with EDTA gave morereduction of dentin compared to sodium hypochlorite. The reduction of VHN ofdentin following the irrigation treatment was statistically significant (p< 0.05 ) .Both sodium hypochlorite and EDTA irrigation solution significantly reduced themicrohardness of root dentin..